MEMORY ENHANCING ACTIVITY OF TAVERNIERA CUNEIFOLIA (ROTH) ARN: A SUBSTITUTE FOR COMMERCIAL LIQUORICE - VIJAY C.JAMDHADE; BABASAHEB S.SURWASE (International Journal of Pharma and Bio Sciences, 2013)
The present study was undertaken to evaluate the potential effect of methanolic and aqueous extracts of Taverniera cuneifolia (Roth) Arn. for cognitive performance activity. Memory impairment was produced by administration of Scopolamine (2 mg/kg i.p) in Swiss albino mice. Elevated plus maze was used to asses learning and memory activity. Taverniera cuneifolia extracts treated group decreased transfer latency in elevated plus maze which is an indicative of cognition improvement. The results of HPTLC and HPLC study of Taverniera cuneifolia indicate the presence of Glycyrrhetinic acid as an active phytochemical constituent. Methanolic and aqueous extracts of Taverniera cuneifolia has been demonstrated to improve cognitive process by enhancing memory in Elevated plus maze. The present study suggests that methanolic and aqueous extracts of Taverniera cuneifolia might have increased brain acetylcholine level and hence it possess memory enhancing activity in Scopolamine induced amnesia model.